2021
DOI: 10.1093/ehjci/jeab211
|View full text |Cite
|
Sign up to set email alerts
|

Right heart chambers geometry and function in patients with the atrial and the ventricular phenotypes of functional tricuspid regurgitation

Abstract: Aims Atrial functional tricuspid regurgitation (A-FTR) is a recently defined phenotype of functional tricuspid regurgitation (FTR) associated with persistent/permanent atrial fibrillation. Differently from the classical ventricular form of FTR (V-FTR), patients with A-FTR might present with severely dilated right atrium and tricuspid annulus (TA), and with preserved right ventricular (RV) size and systolic function. However, the geometry and function of the right ventricle, right atrium, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 38 publications
4
47
0
3
Order By: Relevance
“…Moreover, A-STR patients had a 2.7 lower risk of death for any cause and HF hospitalization compared to V-STR patients. Regarding the different echocardiographic remodeling observed in the 2 population, interesting results regarding RA, TA, and RV remodeling were found, in line with previous evidence ( 8 , 20 , 37 ).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Moreover, A-STR patients had a 2.7 lower risk of death for any cause and HF hospitalization compared to V-STR patients. Regarding the different echocardiographic remodeling observed in the 2 population, interesting results regarding RA, TA, and RV remodeling were found, in line with previous evidence ( 8 , 20 , 37 ).…”
Section: Discussionsupporting
confidence: 90%
“…Recently, a study from our group sought to analyze the TV geometry in a cohort of patients with any degree of TR compared with a control cohort and classified in A- and V-STR on the base of an echocardiographic definition ( 20 ). Contrary to our results, in that study, A-STR patients showed larger RAV min compared to V-STR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings also showed a significant correlation of 3DE TA parameters with maximal RA maximal volume. This is not an unexpected result because it has been proven that an enlarged RA secondary to atrial fibrillation favors TA dilatation and the occurrence of functional TR (2,3,(43)(44)(45)(46)(47). Moreover, we demonstrated that RA maximal volume was independently associated with TA 3D area both at end-diastole and midsystole.…”
Section: Normal Ta Dynamicssupporting
confidence: 72%
“…The adverse RV remodeling may result from any of the aforementioned conditions: pressure overload (pulmonary arterial hypertension, PAH), volume overload (significant tricuspid regurgitation, TR), primary myocardial disease, or a combination of them [ 10 , 19 ]. For example, in DCM patients affected by hereditary muscular dystrophies [ 20 ], RV longstanding volume overload and dysfunction [ 21 ] can develop in the context of a direct atrial myopathic process that contributes to the development of AF, and consecutive atrial secondary TR [ 22 , 23 ].…”
Section: Right Ventricular Dysfunctionmentioning
confidence: 99%